Low Loss, High NA Chalcogenide Glass Fibers for Broadband Mid‐Infrared Supercontinuum Generation. Issue 5 (26th March 2015) - Zhang, Bin; Guo, Wei; Yu, Yi; Zhai, Chengcheng; Qi, Sisheng; Yang, Anping; Li, Lei; Yang, Zhiyong; Wang, Rongping; Tang, Dingyuan; Tao, Guangming; Luther‐Davies, Barry
Abstract : High‐purity Ge–As–Se and Ge–As–S chalcogenide glasses were prepared by modified physical and chemical purification techniques. Using the purified glasses, step‐index fibers with a small core ( 5.5 μm) and large numerical aperture ( 1.3) were fabricated. When a 13.5‐cm‐long fiber was pumped with 320 fs pulses at a repetition rate of 10.5 MHz at 4.1 μm, supercontinuum spanning from 1.8 to 9.8 μm with a dynamic range of ±10 dB and an average power of 3 mW was generated.